MiR‐218 regulates diabetic nephropathy via targeting IKK‐β and modulating NK‐κB‐mediated inflammation. Issue 4 (24th September 2019) - Li, Mo; Guo, Qiushi; Cai, Hanqing; Wang, Haiyang; Ma, Zhiming; Zhang, Xuan
Abstract: Diabetic nephropathy (DN) is a common clinically relevant complication of diabetes that is associated with damage to the capillaries, yet the etiology of this condition remains unclear. Nuclear factor‐kappa B (NF‐κB) activation is known to be associated with DN‐related inflammation and disease progression. Recent work indicated that microRNAs are diagnostic biomarkers of DN progression associated with inﬂammation in the progression of DN. miR‐218 is known to play key regulatory roles in certain cancers in humans, while its influence on DN pathology remains uncertain. The present study, therefore, sought to assess how miR‐218 influences the progression of disease in both a rat streptozotocin‐induced model of DN and as well as an in vitro model system in which mouse podocytes were stimulated with high glucose levels. We found miR‐218 to be markedly downregulated in both model systems relative to appropriate controls, and this downregulation was associated with IKK‐β upregulation. In DN rat model, overexpressing miR‐218 was sufficient to reduce renal injury. We further determined that podocyte proliferation was markedly impaired by glucose treatment, leading to the apoptotic death of these cells, and miR‐218 mimics were able to reduce these phenotypes. Overexpressing miR‐218 also significantly dampened inflammatory responses in this model system, as evidenced by reduced tumor necrosis factor‐α, interleukin‐6 (IL‐6), IL‐1β, and MCP‐1 levels. We then confirmed that miR‐218 targeting the messenger RNA encoding IKK‐β using a dual‐luciferase reporter assay. Together, our results provide clear evidence that miR‐218 regulate NF‐κB‐mediated inflammation, which is central to DN progression. Abstract : miR‐218 is downregulated and IKK‐β is upregulated in diabetic nephropathy rat model. Overexpressing miR‐218 is sufficient to reduce renal injury. miR‐218 regulates inflammatory response by targeting IKK‐β and regulating nuclear factor‐kappa B signaling pathway.